Pemberdayaan Keterampilan Berpikir Kreatif melalui Model Remap Think Pair Share - Miswandi Tendrita; Susriyati Mahanal; Siti Zubaidah (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Creative thinking skills is one of the life skills needed in the 21st century which can be empowered through learning process. That skills can be a provision for students to solve a variety problems, including in science learning. Creative thinking skills can not growed by itself, but need stimulated in the form of learning models that helps empower the skills. One of the learning model that helps empower creative thinking skills was Reading-Concept-Map Think Pair Share (Remap TPS) learning model. The step of Remap TPS have power to enhance student’s creative thinking skills as described. Keywords:        creative thinking skills, Remap-TPS